Pathways to Post-Secondary Success: Applying Situated Expectancy-Value Theory to the Experiences of Students With Disabilities and Their Peers - Goegan, Lauren; Young, Stephanie; Bouchard, Justin; Wood-Warren, Ali (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2025)
The number of Canadians beginning post-secondary education (PSE) each fall continues to grow. One group in particular that is seeing an increase in numbers is students with disabilities (e.g., learning disabilities, attention-deficit/hyperactivity disorder). The purpose of this study was to examine how students broadly, and students with disabilities specifically, can be supported in their PSE journey. Utilizing situated expectancy-value theory (SEVT) as our guiding theory, we examined how the components of expectancy, value, and cost, alongside the attendance of a transition program, supported various student outcomes (i.e., emotions, acquisition of knowledge and skills, GPA, and satisfaction). Our findings highlight the role of both psychosocial factors and institutional support in promoting successful student transitions to PSE. Limitations and future research directions are also discussed.